RELATIONSHIP BETWEEN 3M PLUS BEHAVIOR AND THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER IN INDONESIAN - Latoso, Rudi; Tosepu, Ramadhan; Saptaputra, Syawal Kamiluddin (Preventif Journal, 2024)
ABSTRACT One of the serious public health problems is dengue fever cases, which is influenced by environmental factors. This can influence the increase in larvae-free rates by a percentage of 85%. This is due to a lack of public awareness in carrying out 3M Plus activities regularly. The 3M Plus behavior is closely related to the incidence of dengue hemorrhagic fever in Indonesian people. This research aimed to determine the relationship between 3M Plus behavior and the incidence of dengue hemorrhagic fever in Indonesian people. The research method was carried out by literature review using the Google Scholar database with inclusion criteria free full text manuscript. The languages used were Indonesian and English. The data taken was the articles published from 2016 to 2023. The results were analyzed and obtained in six national journals, which explained that 3M Plus behavior was related to the incidence of dengue hemorrhagic fever in Indonesian people. The 3M Plus behavior that had a dominant relationship to the incidence of dengue fever was the habit of draining and tightly closing water reservoirs. This research can be concluded that the 3M Plus behavior among Indonesian people needs to be optimized in order to reduce the incidence of dengue fever, especially regarding the implementation of 3M Plus behavior among the community. Keywords: 3M Plus Behavior, Incidence of DHF